2010
DOI: 10.1093/jpepsy/jsq093
|View full text |Cite
|
Sign up to set email alerts
|

Mother–Adolescent Agreement Regarding Decision-Making Autonomy: A Longitudinal Comparison of Families of Adolescents with and without Spina Bifida

Abstract: SB and low SES are risk factors for lower levels of agreed-upon decision-making autonomy. Future studies should examine how parent-adolescent agreement regarding autonomy relates to psychosocial outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…Several studies have shown that for adolescents with chronic conditions, the pathway towards independence is often delayed and associated with conflicts. Parental overprotection and a complicated separation process, caused by medical issues, do play a role (Devine et al 2011, Hommel et al 2011. As the interviewees wished to exclude their parents from the workshop, an additional group meeting would give parents the opportunity to benefit from social support, as shown in other studies (Kingsnorth et al 2011, Akre & Suris 2014.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Several studies have shown that for adolescents with chronic conditions, the pathway towards independence is often delayed and associated with conflicts. Parental overprotection and a complicated separation process, caused by medical issues, do play a role (Devine et al 2011, Hommel et al 2011. As the interviewees wished to exclude their parents from the workshop, an additional group meeting would give parents the opportunity to benefit from social support, as shown in other studies (Kingsnorth et al 2011, Akre & Suris 2014.…”
Section: Discussionmentioning
confidence: 97%
“…Parental overprotection and a complicated separation process, caused by medical issues, do play a role (Devine et al . , Hommel et al . , Peeters et al .…”
Section: Discussionmentioning
confidence: 99%
“…The Decision‐Making Questionnaire (DMQ) measures a child's autonomy in decision making by assessing the parent's beliefs regarding the amount of autonomy given to the child within the family on both medical and nonmedical rules . Respondents rate the degree of autonomy for a given rule on a four‐point scale ( 1 = I/We tell my child exactly what to do, 2 = I/We ask my child's opinion about this, but I/We usually have the final say, 3 = I/We leave this up to my child to decide, and 4 = Does not apply) . Cumulative total scores were obtained for nonmedically related rules and medically related rules, with a response of 4 (does not apply) not included in calculations.…”
Section: Methodsmentioning
confidence: 99%
“…For example, there is often a tension between the views of people with disabilities and their parents (particularly adolescents and adults with disabilities) in which the former may want to push for more independence and autonomous decision making and the latter may be somewhat overprotective (Carey, 2009). These tensions are likely to be amplified when adults are coresiding with their parents, which may negatively affect the adult with disabilities and their family caregivers (Devine, Wasserman, Gershenson, Holmbeck, & Essner, 2010), although there is some research that highlights families of adolescents with disabilities experience closer relationships and less family conflict (Hartley, Barker, Seltzer, Greenberg, & Floyd, 2011;Jandazek, DeLucia, Holmbeck, Zebrack, & Friedman, 2009). These issues may vary across racial and ethnic groups in which interdependence is a prized value versus independence (Ben-Moshe & Magaña, 2014).…”
Section: Personal Level: Individuals With Disabilities Individual Camentioning
confidence: 99%